Stationary values of the transmission ratio of the planar fourbar - Wittenburg, J. (Vietnam Journal of Mechanics, 2008)
The transmission ratio of the planar fourbar, i.e. the ratio of the angular velocities of input link and output link, is a function of the input angle. Freudenstein [1] showed how to calculate stationary values of the transmission ratio. In the present paper a new method is described. Like Freudenstein’s method it results in a sixth-order polynomial equation